Managing Industry-Based Curriculum Quality Improvement To Enhance Students’ Competencies In Vocational Education - Mujiono; Akhyak; Prim Masrokan Mutohar (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
The advancement of globalization, the Industrial Revolution 4.0, and Society 5.0 has significantly transformed labor market demands, requiring human resources with strong competencies in both technical (hard skills) and non-technical (soft skills) domains, as well as the ability to adapt to rapid technological changes. In this context, vocational education institutions are expected to align their curricula with industry needs through an industry-based approach. This study aims to analyze the management of quality improvement in industry-based curricula in developing students’ competencies at SMKS Magetan 1 YKP and SMKS 1 Pemda (Ma’arif) Ponorogo. This research employs a qualitative approach with a multi-site study design to gain an in-depth understanding of the processes of planning, implementation, control, and follow-up in curriculum quality improvement. Data were collected through in-depth interviews, participant observation, and documentation. The analysis involved data condensation, data display, interpretation, and cross-site analysis. Data validity was ensured through credibility, dependability, confirmability, and transferability criteria. The findings indicate that the management of industry-based curriculum quality improvement in both schools is implemented systematically, collaboratively, and adaptively. Planning is conducted through a link and match approach with industry, implementation integrates theory and practice through project-based learning and teaching factory, control is carried out through monitoring, evaluation, and quality audits, and follow-up actions involve curriculum refinement, teacher competency development, and sustainable industry partnerships. These findings confirm that industry-based curriculum management enhances the relevance of vocational education and effectively develops students’ competencies.